Case report: One-stage craniectomy and cranioplasty digital workflow for three-dimensional printed polyetheretherketone implant for an extensive skull multilobular osteochondosarcoma in a dog - Hobert, Marc; Sharma, Neha; Benzimra, Caroline; Hinden, Sandro; Oevermann, Anna; Maintz, Michaela; Beyer, Michel; Thieringer, Florian; Guevar, Julien (Frontiers in Veterinary Science, 2024)
Objective: To report a digital workflow for use and long-term outcome of cranioplasty with a 3D-printed patient-specific Polyetheretherketone (PEEK) implant in a 12-y-old German Shepherd dog after surgical removal of an extensive occipital bone multilobular osteochondrosarcoma (MLO).Animal: A 12-year-old neutered female German Shepherd dog was presented with facial deformity, blindness, tetraparesis, and ataxia. Magnetic resonance imaging (MRI) and computed tomography (CT) identified a large skull-based mass extending extra-and intracranially with severe compression of the cerebellum and occipital lobes of the cerebrum.Methods: One-stage decompressive craniectomy using virtual surgical planned 3D-printed craniotomy cutting guides and the Misonix BoneScalpel® and reconstruction with a patientspecific 3D-printed PEEK cranial implant.Results: 3D-printed craniectomy cutting guides allowed an adequate fit of the cranial implant to the original skull. Misonix BoneScalpel® allowed performing a safe and extensive craniectomy. Postoperative CT (8 weeks after surgery) confirmed the PEEK cranial implant to be in place and without implant rejection. Clinically, the neurological examination identified only a right-hind limb delay in proprioception 8 weeks postoperatively, which remained unchanged at 18 months after surgery. Adjunctive treatment included metronomic chemotherapy. Eighteen months after surgery the dog passed away for reasons unrelated to the MLO, no implant-related complications were reported.3D-printed craniectomy cutting guides, patient-specific PEEK cranial implant, and metronomic chemotherapy can lead to a successful long-term outcome in dogs with extensive skull MLO.Clinical Significance: PEEK is an alternative biomaterial that can be used successfully for 53 skull reconstruction.